Effectiveness of the Implementation of Military Criminal Law Against Soldiers Proven to Have Committed Desertion (Case Study of the Decision of the Military Court II-10 Semarang) - Kustiawan, M. Sjaiful; Hanim, Lathifah (Jurnal Hukum Khaira Ummah, 2025)
Desertion is a form of violation of military criminal law committed by a military member by withdrawing from his service obligations without permission or intentionally avoiding carrying out military duties. Provisions regarding desertion are regulated in Article 87 of the Military Criminal Code (KUHPM). Currently, desertion is one of the most prominent forms of violation in the Indonesian National Armed Forces (TNI), this is due to the high number of soldiers committing desertion each year. This thesis aims First, to analyze the factors that cause the occurrence of the crime of desertion. Second, to analyze the effectiveness of the application of military criminal law to soldiers who are proven to have committed desertion. This research method uses an empirical legal research type, with a sociological approach and the object of study focuses on legal effectiveness. Based on the research results, the factors that cause the occurrence of criminal acts of desertion are based on an analysis of 20 sample decisions from the II-10 Military Court Semarang. It was found that there were several factors causing soldiers to desert, but the biggest factor causing soldiers to desert was due to economic problems, namely debt. The effectiveness of the application of military criminal law against soldiers who are proven to have deserted is based on several factors, as follows: the law regulating desertion is clearly stated and easy for soldiers to understand. Law enforcers who handle desertion cases have the ability, consistency and integrity in handling desertion crimes. The facilities and infrastructure owned are in good condition and adequate for use. Public awareness or legal awareness of soldiers, the majority of soldiers who deserted have known about the prohibitions and sanctions for desertion, the culture in the Criminal Code which reflects Indonesian cultural values, in general, the application of military criminal law against soldiers proven to have deserted has been carried out effectively.